PERAN PROGRAM MAHASISWA WIRAUSAHA (PMW) DALAM MENINGKATKAN PENGETAHUAN BERWIRAUSAHA MAHASISWA FT UNP - 1189-1205 , Oki Nanda Saputra (Universitas Negeri Padang, 2016)
ABSTRACTThis descriptive study aimed to determine the development of entrepreneurship skills of students who follow the Student Entrepreneurial Program (PMW) which is viewed from 7 knowledge entrepreneurship that knowledge to determine the direction of effort, knowledge manage time, knowledge, initiative, knowledge, motivation, knowledge, self-confidence, knowledge, dare to take risks, and knowledge to be responsible.The population in this study were participants engineering students Student Entrepreneurial Program (PMW) in the period 2015-2016 and 2014-2015 development period, then the sample in the study using Taro Yamane formula thus obtained sample of 33 people. Data were collected using a questionnaire with Likert scale.From the results, level of knowledge determines the direction of efforts by both categories, the knowledge to manage time good enough category, knowledge initiative with good category, knowledge motivated with excellent category, knowledge confidently with good enough category, knowledge took a risk by category quite well and knowledge to be responsible with the category quite well, so it concluded the level of knowledge of entrepreneurship students participating in Student Entrepreneurial Program at the FT UNP in the category quite well.Keywords: entrepreneur students program, knowledge, entrepreneur.